Polymorphisms in DNA repair genes, traffic‐related polycyclic aromatic hydrocarbon exposure and breast cancer incidence. Issue 2 (6th April 2016) - Mordukhovich, Irina; Beyea, Jan; Herring, Amy H.; Hatch, Maureen; Stellman, Steven D.; Teitelbaum, Susan L.; Richardson, David B.; Millikan, Robert C.; Engel, Lawrence S.; Shantakumar, Sumitra; Steck, Susan E.; Neugut, Alfred I.; et al.
Abstract : Vehicular traffic polycyclic aromatic hydrocarbons (PAHs) have been associated with breast cancer incidence in epidemiologic studies, including our own. Because PAHs damage DNA by forming adducts and oxidative lesions, genetic polymorphisms that alter DNA repair capacity may modify associations between PAH‐related exposures and breast cancer risk. Our goal was to examine the association between vehicular traffic exposure and breast cancer incidence within strata of a panel of nine biologically plausible nucleotide excision repair (NER) and base excision repair (BER) genotypes. Residential histories of 1, 508 cases and 1, 556 controls were assessed in the Long Island Breast Cancer Study Project between 1996 and 1997 and used to reconstruct residential traffic exposures to benzo[a]pyrene, as a proxy for traffic‐related PAHs. Likelihood ratio tests from adjusted unconditional logistic regression models were used to assess multiplicative interactions. A gene‐traffic interaction was evident ( p = 0.04) for ERCC2 (Lys751); when comparing the upper and lower tertiles of 1995 traffic exposure estimates, the odds ratio (95% confidence interval) was 2.09 (1.13, 3.90) among women with homozygous variant alleles. Corresponding odds ratios for 1960–1990 traffic were also elevated nearly 2–3‐fold for XRCC1 (Arg194Trp), XRCC1 (Arg399Gln) and OGG1 (Ser326Cys), but formal multiplicative interaction was not evident. When DNA repair variants for ERCC2, XRCC1 and OGG1 were combined, among women with 4–6 variants, the odds ratios were 2.32 (1.22, 4.49) for 1995 traffic and 2.96 (1.06, 8.21) for 1960–1990 traffic. Our study is first to report positive associations between traffic‐related PAH exposure and breast cancer incidence among women with select biologically plausible DNA repair genotypes. Abstract : What's new? Polycyclic aromatic hydrocarbons are known carcinogens generated by vehicular traffic. They damage DNA by forming adducts or inducing oxidative stress. Here the authors examined the association between traffic exposure and breast cancer incidence while taking into account different DNA repair genotypes. Cancer risks were elevated in women carrying certain DNA repair variants especially when some variants were combined. These findings may help identify women who are particularly susceptible to the carcinogenic effects of traffic pollution on the breast.